2016
DOI: 10.1017/s0031182016000895
|View full text |Cite
|
Sign up to set email alerts
|

Central European parasitic flatworms of the family Renicolidae Dollfus, 1939 (Trematoda: Plagiorchiida): molecular and comparative morphological analysis rejects the synonymization ofRenicola pinguiscomplex suggested by Odening

Abstract: The Renicolidae are digenean parasites of piscivorous and molluscivorous birds. Although they exhibit few morphological autapomorphies and are highly variable, the numerous suggested re-classifications within the family have never been supported by any molecular analyses. We address the possible synonymization of species within the Renicola pinguis complex suggested previously by Odening. We provide and analyse sequences of two nuclear (ITS2, 28S rDNA) and two mitochondrial (CO1, ND1) DNA loci of central Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…In the ITS2 region, the high nt similarity among R. sloanei strains from P. puffinus of this study (100%) may be due to the parasitism of the same species as the definitive host. In addition, the strains presented less nt similarity (95.9%) with the other R. sloanei strains described previously by Heneberg et al (2016) in S. demersus.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In the ITS2 region, the high nt similarity among R. sloanei strains from P. puffinus of this study (100%) may be due to the parasitism of the same species as the definitive host. In addition, the strains presented less nt similarity (95.9%) with the other R. sloanei strains described previously by Heneberg et al (2016) in S. demersus.…”
Section: Discussioncontrasting
confidence: 59%
“…According to the morphological findings described by Wright (1956) and the phylogenetic analysis performed in this study, it can be suggested that C. pythionike is a metacercariae of R. sloanei, since it has the close nt similarity with R. sloanei of P. puffinus (96.6%) (described herein) and with R. sloanei of S. demersus (96.2%) (HENEBERG et al, 2016). In addition, C. pythionike, when compared to other renicolid strains, showed a reduced nt similarity with R. sternae (69.2%), R. lari (68.4%), and R. pinguins (74.6%).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…3) demonstrated that the species sequenced in this study is a member of the genus Renicola. Although 28S sequence data have been provided for three fully identified species of the genus Renicola [49], these sequences fail to align properly with those produced for renicolids in this or any other study [27,[50][51][52][53]. Because of this, we did not incorporate these 28S rDNA data into our phylogenetic analyses.…”
Section: Molecular Analysesmentioning
confidence: 99%